Frequency of full, partial and no recovery from subsyndromal deliriumin older hospital inpatients. (2nd November 2015) - Cole, Martin G.; Bailey, Robert; Bonnycastle, Michael; McCusker, Jane; Fung, Shek; Ciampi, Antonio; Belzile, Eric
Abstract : Objectives: To determine the frequencies of full, partial and no recovery from subsyndromal delirium (SSD) in older hospital inpatients. A secondary objective was to compare the recovery status of patients with SSD or delirium. Methods: SSD was defined as acute onset of one or more Confusion Assessment Method core symptoms of delirium (fluctuation, inattention, disorganized thinking and altered level of consciousness) not meeting criteria for delirium and not progressing to delirium. The recovery status of medical or surgical inpatients aged 65 and older with SSD was assessed approximately 1 and 3 months after enrolment. Primary outcome categories were full recovery (no core symptoms of delirium), partial recovery (presence of one or more core symptoms but fewer symptoms than at enrolment), no recovery (same number of core symptoms as at enrolment) or death. Nominal logistic regression was used to compare the recovery status of patients with SSD or delirium. Results: Twenty‐eight patients with SSD were enrolled. At the first follow‐up, the frequencies of full, partial and no recovery and death were 40%, 12%, 32% and 16%, respectively; at the second follow‐up, the frequencies were 54%, 8%, 21% and 17%, respectively. The frequency of full recovery was much higher in patients with SSD than delirium. Conclusion: Small study sample size notwithstanding, the majority (54%) of patients with SSD recovered fully, but a substantial proportion (29%) had a protracted course. It may be important to monitor the longer‐term course of SSD and develop strategies to ensure full recovery in all patients. Copyright © 2015 John Wiley & Sons, Ltd.